La Révolution, les fêtes et leurs images - Guillaume Mazeau (Images Re-Vues)
Is it possible to throw a new glance on French Revolution festivals? This events have been mainly studied through written sources, which stressed the influence of the utopian model of the "revolutionnary festival", relying upon collective emancipation or, on the contrary, folkloric rituals symbolized by the Bicentenary(1989).  This article claims that such events should be studied through images and fully included in the political antropology of the French Revolution, based on visual culture and experience. If we see them as public spectacles and collective performances, the French Revolution festivals reveal their functions in a context of collective crisis: the helped to shape new forms of citizenship and collective representation.